Directing : film techniques and aesthetics - Rabiger, Michael; Hurbis-Cherrier, Mick; Mercado, Gustavo (Oxon Routledge, 2020)
"Directing: Film Techniques and Aesthetics is a comprehensive exploration into the art and craft of directing for film and television. It's filled with practical advice, essential technical information, and inspiring case studies for every stage of production. This book covers the methods, technologies, thought processes, and judgments that a director must use throughout the fascinating process of making a film, and concentrates on developing the human aspects of cinema to connect with audiences. The fully revised and updated 6th edition features new sections on using improvisation, the development of characters for long form television series, visual design, the role of the digital imaging technician, film promotion and distribution, alongside expanded information on contemporary color grading tools, stylistic approaches and genre, workflows, blocking scenes for the camera and more. The book emphasizes independent and short form cinema which allows cutting-edge creativity and professionalism on shoestring budgets. Recognizing that you learn best by doing, it includes dozens of practical hands-on projects and activities to help you master technical and conceptual skills. Just as important as surmounting technological hurdles is the conceptual and authorial side of filmmaking. This book provides an unusually clear view of the artistic process, particularly in working with actors and principle crew members. It offers eminently practical tools and exercises to help you develop your artistic identity, find credible and compelling stories, choose and work with your cast and hone your narrative skills. Directing shows you how to surpass mere technical proficiency and become a storyteller with a distinctive voice and style. The accompanying companion website includes film analysis exercises, shooting projects, checklists and assignment forms, analytical questionnaires, updated production forms and logs for all phases of a project with links to additional resources and set safety advice"--
The world of the film director -- Developing as a director -- Essential elements of drama -- Shaping the story into drama -- Plot, time, and structure -- Screenplay ground rules -- Recognizing the superior screenplay -- Script analysis and development -- Cinematic point of view -- Form and style -- Tone, style and genre -- Film language -- The frame and the shot -- The moving camera -- Language of the edit -- The human vantage of cinematic language -- Exploring the script -- Casting -- Acting fundamentals -- Directing actors -- Rehearsals -- Acting exercise -- Planning the visual design -- Developing the shooting script -- Line producing and logistics -- Developing a production crew -- The director and production tech -- On set : production begins -- Directing on the set -- Monitoring continuity and progress -- Postproduction overview -- Editing begins : getting to know the footage -- The rough cut -- Getting to fine cut and picture lock -- Working with music -- The finishing touches -- Getting it out there.
Includes index.
Includes Filmography.
Keywords: Motion pictures -- Production and direction; Motion pictures -- Aesthetics